Welding residual stress in roots between deck plate and U-rib in orthotropic steel decks. (October 2016) - Kainuma, Shigenobu; Jeong, Young-Soo; Yang, Muye; Inokuchi, Susumu
Highlights: The residual stress at weld root was examined depend on partial penetration weld. The weld residual stress was measured by cutting and the magnetostriction method. The residual stress distributions were compared to experiment and FE analysis. The thermo-elastic-plastic FE analyses were carried out on parametric models. Abstract: Fatigue cracks have recently been observed at weld roots between the deck plate and U-rib in orthotropic steel decks. Some cracks initiated from the weld roots and then propagated through the deck plate. The welding residual stress at the root appears to have a considerable influence on crack initiation and propagation. However, the stress has not yet been efficiently clarified in previous studies. In this study, the residual stress of model specimens with or without weld penetration and root gap were measured using the cutting method and magnetostriction method. In addition, thermo-elastic-plastic finite element analyses were carried out on parametric models of actual welded joints.